Comparison of Mobile Banking Service Quality on Customer Satisfaction Between Bank Muamalat and Bank Syariah Indonesia - Syakir, Dina Fikriyah (Adpebi Science Series, 2022)
The purpose of this study is to determine the quality of mobile services banking has an effect on customer satisfaction and know the different service quality on customer satisfaction with the object of research are Bank Muamalat Branch Makassar and Bank Syariah Indonesia (BSI) Branch Pannampu. This research uses associative-comparative research, with a quantitative approach. The data used for this research is primary data. The data collection technique used is a questionnaire, with 100 respondents as the sample. The hypothesis testing of this study uses t-test statistics, with a man-Whitney test ranking. The results obtained from the current study state the quality of mobile banking service has a positive and significant effect on customer satisfaction in Bank Muamalat Indonesia Branch Makassar with a sig value of 0.000 and the quality of mobile banking services has a positive and significant effect on customer satisfaction of Bank Syariah Indonesia Branch Pannampu with a sig value of 0.000. Meanwhile, there are differences in the quality of m-banking services to customer satisfaction at Bank Muamalat Branch Makassar with a value of 39.66 (39%) and Bank BSI Branch Makassar Pannampu with a value of 61.34 (61%). This means that the quality of m-banking services to customer satisfaction at Bank BSI Branch Pannampu Makassar is more than the Bank Muamalat Branch Makassar. Keywords: Service Quality, Mobile Banking, Customer Satisfaction, Shariah Banking